Challenges for the consumption of fruits and vegetables: Desafíos para el consumo de frutas y verduras - Rodriguez Leyton, Mylene (2019)
Objective: Identify the challenges to face in order to improve the low consumption of fruits and vegetables in Colombia. Methods: Documentary, descriptive and exploratory research carried out in 2016 and 2017, based on the search, selection and revision of bibliographic references to analyze and reflect on the indicators of consumption and production of fruit and vegetable consumption and to identify the challenges to reach WHO recommendations based on scientific evidence. Results: the nutritional contribution of fruits and vegetables and their benefits for human health is reaffirmed, followed by production and consumption indicators as a topic of public health interest; the rules and guidelines of public policy that promote the consumption of healthy eating as a lifestyle are reviewed and the main challenges that sectors such as the food industry, gastronomy, government, public social and sectorial policies in health, education, agriculture, social promotion, communication, as well as the academy; to define effective strategies to increase the consumption indicators of fruits and vegetables and to achieve the goals of a minimum percapita consumption of 5 servings or 400 g per day proposed by the World Health Organization (WHO). Conclusion: Several countries, have been providing technical guidelines to encourage the consumption of fruits and vegetables; however, it is advisable to carry out periodic monitoring of the indicators, perform outcome and impact evaluations and research aimed at identifying the causes of low consumption and designing effective strategies appropriate to the context of the populations. DOI:10.25176/RFMH.v19.n2.2077